Mapping Of Tuberculosis Areas In West Java Province In 2023 - Marenza, Viko Iqra (Tadulako University, 2025)
Tuberculosis is infectious disease caused by the bacteria Mycobacterium tuberculosis that spreads through the air. Mapping the distribution of tuberculosis cases in West Java through the use of Geographic Information System (GIS) applications, by classifying the variables of tuberculosis cases and their risk factors at the provincial level in 2023. This research is a descriptive qualitative study using secondary data from the health profile of West Java Province and population data from the West Java Central Bureau of Statistics. Data management and map making will use the Quantum GIS application version 3.34. In analysing and interpreting the data, classification will be carried out on each variable to be studied. In classifying the data, natural breaks jenks will be used. In the results of the research in West Java province, there are 3 areas with very high TB susceptibility categorised as Bogor, Cimahi City and Bandung City. And there are 6 regions with very low susceptibility categories Purwakarta, Subang, Sumedang, Ciamis, Banjar City and Pangandaran. The limitations of the data and variables studied affect the results of the analysis and are not comprehensive, therefore in future studies other variable factors can be classified to obtain a more comprehensive picture of tuberculosis vulnerability.